THE INFLUENCE OF FINANCIAL LITERACY, LIFE STYLE, INCOME, AND LOCUS OF CONTROL ON THE CONSUMER BEHAVIOR OF SHOPEE PAYLATER USERS (CASE STUDY OF STUDENTS IN PEKANBARU) - Fina Ananta Bangun; Poppy Camenia Jamil (Jurnal Apresiasi Ekonomi, 2025)
The study aims to determine how financial literacy, lifestyle, income, and locus of control affect the consumer behavior of Shopee Paylater users, spescifically among student in  Pekanbaru. The method used in this research is quantitative, and the data analysis technique employed is. The sample consists of 136 student respondents who are Shopee Paylater users. Data collection was conducted through the distribution of questionnaires using a Likert scale. The data analysis method used is multiple linear regression for hyphothesis testing, utilizing the SPSS program. The results of this study indicate that financial literacy and income do not have a significant effect (0.130 and 0,549), while lifestyle has a significant positive impact (0.000). Locus of control shows a tedency to influence, although it is not significant. The simultaneous test confirms that these variables collectivelly have a significant impact, with lifestyle being the primary driver of consumer behavior.